Neuronal cytoskeletal dynamic modification induced by unconjugated bilirubin - Coutinho, Eduarda Cristina Duarte de Magalhães (2010)
Tese de mestrado, Biologia (Biologia Molecular Humana), 2009, Universidade de Lisboa, Faculdade de Ciências